Assessment of Dyeing Properties of Novel Bisazo-Bisazomethine Disperse Dyes on Polyester Fabric - B. C. Dixit; D. M. Patel (E-Journal of Chemistry)
Novel bisazo-bisazomethine disperse dyes were prepared by the coupling of diazotized solutions of various aromatic amines with 2,2'-{sulfonylbis [4,1-phenylene nitrilomethylylidene]} diphenol (SB). Above Schiff base was prepared by the condensation of 2-hydroxybenzaldehyde with 4,4’-sulphonyl- dianiline (Dapson). The resultant dyes were characterized by elemental analysis, IR and1H NMR spectral studies. The UV Visible absorption spectral data were investigated in dimethylformamide (DMF) and are discussed in terms of structural property relationship. Their dyeing performance as disperse dyes has been assessed on polyester fabrics. The results show that a better hue was obtained on polyester fabrics and have mild to moderate fastness properties.